Status of research on building pathology: a bibliometric analysis - Porras-Alfaro, David (2020)
This article contributes to the state of research in construction pathology, a topic little developed in Costa Rica, but with the potential to generate applied and contextualized research to the particularities in the country. Methodologically, the article was based on a bibliometric study carried out from the Scopus database and analyzed through the Bibliometrix program.  The main results of the study were 268 records of publications associated to the search terms “building pathology”, “construction pathology” and “patología de la construcción”, covering a period from 1983 to 2020 and the journals were the source of greatest recurrence in terms of publications. From the analysis of the keywords, associated themes were determined such as: buildings, concrete, walls, historical preservation, construction, non-destructive techniques, among others. Jorge De Brito stands out among the authors with the greatest number of publications, with the highest H index. With regard to the origin of scientific production, Spain stands out with a total of 147 contributions, and is also the country with the greatest number of international collaborations. It is concluded that the greatest scientific production on construction pathology has been focused on the last decade, produced in English, and Spain being the country with the greatest contribution. The link between construction pathology and areas such as heritage restoration, non-invasive techniques and construction materials, mainly concrete, is evident.